Predictive value of NLRC3 levels for pulmonary hypertension in patients with chronic obstructive pulmonary disease - Yılmaz, Meltem; Mutlu, Levent Cem; Alpsoy, Şeref; Akyüz, Aydın; Çelikkol, Aliye; Kaymaz, Özlem (The European Research Journal, 2024)
Objectives: Chronic obstructive pulmonary disease (COPD) is a medical condition defined by persistent airflow limitation and respiratory symptoms caused by airway and/or alveolar abnormalities. Pulmonary hypertension (PH) is one of the cardiovascular comorbidities associated with COPD. We investigated the correlation of NLRC3 levels in patients with COPD with prognostic and surrogate parameters of PH on echocardiography and examined whether it could be used to predict PH in this patient population. Methods: A total of 80 patients diagnosed with COPD and 40 healthy volunteers as the control group were included in the study. The COPD group was further divided into two subgroups according to the systolic pulmonary artery pressure (sPAP) as follows: sPAP